2013
DOI: 10.1161/circresaha.113.301071
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibition Attenuates Transcriptional Activity of Mineralocorticoid Receptor Through Its Acetylation and Prevents Development of Hypertension

Abstract: Human nuclear receptor superfamily has 48 members, among which the androgen receptor (AR), the estrogen receptor (ER), the progesterone receptor, the glucocorticoid receptor (GR), and the mineralocorticoid receptor (MR) belong to the steroid receptor family. 12 The transcriptional activity of steroid receptors is mainly regulated by ligand; however, post-translational modifications, such as phosphorylation, acetylation, ubiquitylation, and sumoylation, also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 39 publications
8
104
0
Order By: Relevance
“…3). Acetylation of lysine in the hinge region of MR resulted in transcriptional repression of MR (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Acetylation of lysine in the hinge region of MR resulted in transcriptional repression of MR (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, post-transcriptional modifications, such as acetylation, phosphorylation, ubiquitylation, and sumoylation, play critical roles in regulating its transcriptional activity (Faus and Haendler, 2006). Phosphorylation of MR enhances its binding affinity for DNA response elements (Massaad et al, 1999), whereas acetylation of MR inhibits recruitment of MR and RNA polymerase II (Pol II) on promoter of MR target genes and prevents development of hypertension (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Welsbie et al (39) determined that KDACs 1 and 3 were largely responsible for promoting androgen receptor transactivation in LNCaP cells, whereas KDAC3 has been shown to potentiate mineralocorticoid receptor transactivation in HEK293 cells (40). Several studies suggest a positive relationship between KDAC activity and promoter association of RNA polymerase (pol) II.…”
Section: Discussionmentioning
confidence: 99%
“…A consensus glucocorticoid response element (GRE) is located at position K429/K414 in the human serum-and glucocorticoid-regulated kinase 1 (Sgk1) promoter; chromatin immunoprecipitation (ChiP) data have shown that MR directly binds this region of the Sgk1 gene and stimulates its transcription in embryonic kidney 293 cells (HEK293) (Lee et al 2013). SGK1 has been shown to mediate aldosteroneinduced NaC reabsorption by renal epithelia (McCormick et al 2005), but a role for Sgk1 has been also demonstrated in adipocyte differentiation (Di Pietro et al 2010).…”
Section: Role Of Mr In Regulating Adipogenesis-linked Signaling Pathwaysmentioning
confidence: 99%